The Synergistic Effect of Copper Nanoparticles and Vancomycin in Vitro and in Vivo - Zahraa H.Kadhim, Mais E. Ahmed, Ilker Şimşek (Pakistan Journal of Medical & Health Sciences, 2022)
A new synergistic nanoparticle green synthesis from Vancomycin and CuoNPs techniques and evaluation effect invite anti- bacteria resistance methicillin-resistant S. aureus with zone of inhibition reached 20mm and characterization included UV-Visible, TEM , SEM and X-ray. rating at various concentrations (512, 256,128,64,32 and 16) μg/ml. The synergistic nanoparticle (CuoNPs) and are minimal toxicity, biology safety and antibacterial.the wound healing skin after 7 day after tretmant 64 μg/ml . Keywords: Synergistic, Vancomycin, CuoNps